EFFECTIVENESS OF BASIC PRE-HOSPITAL LIFE SUPPORT TRAINING FOR AMBULANCE PERSONNEL: A LITERATURE REVIEW - Syukri, Muhammad; NLP Inca Buntari Agustini; Ni Made Dewi Wahyunadi; Yustina Ni Putu Yusniawati (Nursing Sciences Journal, 2025)
Medical emergencies remain the leading cause of death worldwide, with most occurring in the pre-hospital phase. Ambulance personnel play a vital role in providing initial assistance, requiring basic skills through Basic Pre-Hospital Life Support (BPHLS) training. The purpose of this study was to review the effectiveness of BPHLS training in improving the competence of ambulance personnel through a literature review. This study is a a systematic literature review based on PRISMA guidelines. Searches were conducted in PubMed, ScienceDirect, and Google Scholar for articles published between 2018 and 2024. Of the 152 articles identified, 12 articles met the inclusion criteria and were analyzed narratively. The results of the study showed that most studies showed that BPHLS training improved the knowledge, skills, confidence, and behavior of ambulance personnel in handling emergencies. Simulation-based training methods were more effective than lectures. However, several studies reported a decline in skills within 6–12 months without refresher training, and the impact on patient clinical outcomes was still inconsistent. BPHLS training has been proven effective in improving the competence of ambulance personnel, but it needs to be conducted regularly, be standardized nationally, and be supported by quality facilities and instructors. It is recommended that there be periodic refresher training programs and integration of training into the education system and pre-hospital services.